Formulation and Effectiveness Test of Liquid Soap from Siam Weed (Chromolaena odorata (L.) Leaves Ethanol Extract Against Staphylococcus aureus - Diana, Vivi Eulis; Abadi, Hafizhatul; Andry, Muhammad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Chromolaena odorata (L.) is one of the plants known as weeds. Alkaloids, flavonoids, saponins, tannins, and glycosides are active chemicals found in Siam weed leaves. The study aimed to see if an ethanol extract of Siam weed leaves can be made into liquid soap and has antibacterial action against Staphylococcus aureus germs. The liquid soap of Siam weed (Chromolaena odorata L.) leaf ethanol extract at concentrations of 3%, 6%, and 9% was carried out experimentally in the laboratory, along with physical liquid soap evaluation tests such as organoleptic test, homogeneity test, pH test, foam height test, specific gravity test, test irritation, and hedonic test. Staphylococcus aureus bacteria were then tested. The assessment test criteria were met by making liquid soap preparations of ethanol extract of Siam weed leaves at concentrations of 3%, 6%, and 9%. The color of the solid soap was brown - dark brown, and the texture was liquid with a lemon scent; the homogeneity test showed that all preparations were homogeneous; the pH test of the soap was 9.1 -9.7; the foam height test was 53-66 mm; the specific gravity test was 1-1.01 g/ml; and the irritation test revealed that all preparations had no reaction to redness, itching, and swelling on the skin. The hedonic test on skin revealed that all preparations obtained favorable evaluations from the panelists. The antibacterial activity of liquid soap against Staphylococcus aureus germs was F1 3.65 mm, F2 5.75mm, and F3 6.5mm. Based on the results of the Staphylococcus aureus test, it could be concluded that in the formula F1 (3% concentration), F2 (6% concentration) and F3 (9% concentration) had an inhibition zone.